Tipos de bioinsumo a base de microalga Chlorella vulgaris na produção de mudas de manjericão - Oliveira Barbosa , Alessa; ferreira da Silva Binotti , Flávio; Victor Oliveira Duarte, João; Alves Fette, Isabella; Duarte Cardoso Binotti , Eliana; Costa , Edilson (ANAIS DO ENIC, 2026)
-